Observation of two-beam collective scattering phenomena in a Bose-Einstein condensate - Dimitrova, Ivana (2017)
Different regimes of collective light scattering are observed when an elongated Bose-Einstein condensate is pumped by two noninterfering beams counterpropagating along its long axis. In the limit of small Rayleigh scattering rates, the presence of a second pump beam suppresses superradiance, whereas at large Rayleigh scattering rates it lowers the effective threshold power for collective light scattering. In the latter regime, the quench dynamics of the two-beam system are oscillatory, compared to monotonic in the single-beam case. In addition, the dependence on power, detuning, and atom number is explored. The observed features of the two-beam system qualitatively agree with the recent theoretical prediction of a supersolid crystalline phase of light and matter at large Rayleigh scattering rates.